Consignment accounting - a tool of mitigating loss of cargo in shipping industry - Othman, Mahdy S. (Edelweiss Applied Science and Technology, 2025)
This research aims to find out whether consignment accounting is an effective weapon in combating high rates of cargo loss in the shipping sector. The study’s objectives are to evaluate the extent of consignment accounting in managing the probability of cargo loss for countries like Jordan, Norway, Greece, Denmark, and the Middle East. Six hundred respondents were included in the study and data was recorded on the frequency and severity of cargo loss in addition to respondent satisfaction before and after the use of consignment accounting. The data was analyzed using descriptive statistics, paired sample t-tests, ANOVA, Pearson’s correlation, and multiple regression analysis. There are three significant findings that we observed: CONSA group results indicated that consignment accounting implemented decrease the cargo loss percentage throughout all the regional locations we studied; nevertheless, Norway and Denmark show the identical is leading overall, meaning this new accounting technique has an extraordinary performance in avoiding cargoes from being lost. The study found a positive significant relationship between the intensity of consignment accounting adoption and decrease in cargo loss. Simvely, the study finds that the accounting consignment is a useful approach to reducing loss in cargo, particularly in areas that experience more frequent losses. Furthermore, high levels of adoption are related to high satisfaction levels and thus the increased use of the system is advantageous to the shipping industry.